GAMBARAN PENGETAHUAN TENTANG FAKTOR RISIKO DAN PENCEGAHAN KANKER SERVIKS PADA PASIEN WANITA YANG SUDAH MENIKAH DI PUSKESMAS LALANG - PUTRI MAULIA AMAMI HARUN; ANDRI YUNAFRI (JURNAL ILMIAH SIMANTEK, 2021)
Cervical cancer is a malignant tumor that affects the surface layer of the cervix, called squamous epithelial cells, which arelocated between the uterus and the vagina. It has been proven that the main cause of cervical cancer is Humanpapillomavirus (HPV), oncogenic subtypes, especially subtypes 16, 18, 31, 33, and 45. Mortality and morbidity of womenwith cervical cancer is very high, this situation will have a negative impact on world health in the world. including inIndonesia. It is important for women to know what factors can cause cervical cancer and have knowledge about cervicalcancer prevention because of the large incidence of cervical cancer in Indonesia, and there are still many women who do nothave less knowledge. The study design was descriptive with a sample of 45 people. The sampling technique used totalsampling. The data will be analyzed by quantity test using SPSS software. This study shows that the largest age range is inthe age group 36-45 years (late adults) as many as 19 people (42.2%), more respondents with primary school education are17 people (37.8%), the respondent's occupation group Most were housewives (IRT) as many as 34 people (75.6%), morehad knowledge of good cervical cancer risk factors as many as 31 people (68.9%), more had adequate / moderateknowledge of cervical cancer prevention 25 people (55.6%). There are more respondents who have good knowledge aboutcervical cancer risk factors, while more respondents have sufficient / moderate knowledge about cervical cancer prevention.